Anna Karenina : a novel in eight parts - Tolstoy, Leo, graf, 1828-1910 (Viking Penguin, 2001)
A new translation of Leo Tolstoy's novel "Anna Karenina", in which a woman of fine nature forsakes her husband for a lover, and after a bitter experience commits suicide.